ETHANOL PRODUCTION FROM SAGO FERMENTATION USING Saccharomyces cerevisiae AND GELATIN AS A SOURCE OF NUTRIENT FOR MICROBA - -, Firmansyah; Sitorus, Saibun; Kartika, Rudi (Jurusan Kimia FMIPA UNMUL, 2019)
Ethanol from sago flour through fermentation using Saccharomyces cerevisiae and gelatin as nutrition for microbe have been done. The making of ethanol through processes of hydrolysis, fermentation, distillation and analysis of ethanol concentration using Gas Chromatography instrument. The hydrolysis process of sago flour are used two steps which is liquification and saccharification using alpha-amylase and glucoamylase which will convert the starch into glucose. The fermentation process of glucose are done with time variation 5, 6, 7 and 8 days to the concentration variation of gelatin addition which is 0,5 %, 1 % and 1,5 % (w/v) as nutrition source for microbe. The obtained ethanol from fermentation process are purified through distillation. Furthermore, analysis of ethanol concentration are used Gas Chromatography. The analysis results are showed the highest ethanol concentration obtained in 7 days with gelatin addition 1,5 % are 79,50 %.